2009
DOI: 10.4065/84.6.501
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a System-Wide Protocol for Elective and Nonelective Coronary Angioplasty at Sites Without On-site Surgery: The Mayo Clinic Experience

Abstract: OBJECTIVE:To compare outcomes of percutaneous coronary interventions (PCIs) at 2 community hospitals without on-site surgery (Franciscan Skemp Healthcare and Immanuel St. Joseph's Hospital) with a center with on-site surgery (Saint Marys Hospital). PATIENTS AND METHODS:Using a matched case-control design, we studied 1842 elective and 667 nonelective PCI procedures (myocardial infarction [MI]/cardiogenic shock) performed from January 1, 1999, through December 31, 2007. The quality assurance protocol included op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
1
34
0
2
Order By: Relevance
“…Риск смерти, связанный с этой проце-дурой при СИБС, составляет <0,5% [380][381][382]. Эффективность ЧКВ при СИБС, по сравнению с медикаментозной терапией и КШ, была всесто-ронне изучена.…”
Section: чрескожное коронарное вмешательствоunclassified
“…Риск смерти, связанный с этой проце-дурой при СИБС, составляет <0,5% [380][381][382]. Эффективность ЧКВ при СИБС, по сравнению с медикаментозной терапией и КШ, была всесто-ронне изучена.…”
Section: чрескожное коронарное вмешательствоunclassified
“…13,14,17,18,22,24,27,28 All 9 studies reported group size and clinical outcomes according to PCI type. The proportion with 3-vessel disease was relatively higher in 7 studies than in other studies, 7,13,15,17,21,22,27 ranging from 33.6% to 61.5% across these studies. The proportion with left main vessel PCI was reported by only 8 studies and was very low, ranging from 0.4% to 3.8% across these studies.…”
mentioning
confidence: 99%
“…Among these citations, 39 articles were retrieved for full review; 23 met inclusion criteria ( Figure 1). 2,3,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] …”
mentioning
confidence: 99%
“…Recommendations for case selection at facilities without on-site surgery are shown in Table V, and criteria for identifying high-risk lesions and patients are contained in Table VI. There are statistical models for identifying PCI patients at higher risk for mortality or emergency CABG that could be helpful for identifying patients who should not undergo PCI at facilities without on-site surgery [18,71]. However, these models have not been tested or applied on a large scale to determine the advisability of performing a PCI at facilities without on-site surgery.…”
Section: Requirements For Off-site Surgical Backupmentioning
confidence: 99%
“…Since 2006, 11 original studies and 3 meta-analyses on the topic of PCI without on-site surgery have been identified by a computerized systematic literature search using Medline (PubMed and Ovid) and Cochrane Databases [9,[11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%